Seaweed enrichment of feed supplied to farm‐raised Atlantic salmon ( Salmo salar) is associated with higher total fatty acid and LC n‐3 PUFA concentrations in fish flesh - Wilke, Toine; Faulkner, Simon; Murphy, Laura; Kealy, Laura; Kraan, Stefan; Brouns, Fred (European Journal of Lipid Science and Technology, 2015)
Abstract Seaweeds have great potential as feed ingredients for fish farming, though their effects on the fatty acid content and profile of fish flesh are not well established. Recent studies suggest that seaweed supplementation can increase the concentration of long chain omega‐3 PUFA (LC n ‐3 PUFAs) in various animal species, though this effect has never been assessed in salmon. Primarily, this study compared the fatty acid profiles of Atlantic salmon ( Salmo salar ) that were fed a high quality diet containing seaweed (Diet A), with those on a high quality control diet without seaweed (Diet B). In addition, fatty acid profiles of Atlantic salmon that were fed a standard industrial quality diet containing seaweed (Diet C), were compared to those on a similar diet without seaweed (Diet D). Total fatty acid concentrations were significantly higher (+30%, p <0.05) in the flesh of the fish that were fed seaweed. Flesh concentrations of eicosapentaenoic acid (EPA) and DHA were 30% and 62% higher ( p <0.05) in Diet A and Diet C groups compared to salmon in Diet B and Diet D groups respectively. Analysis of the fish lipid revealed no significant differences in LC‐3 PUFAs between the high quality diet groups, while significantly higher (+ 45%, p <0.005) concentrations EPA + DHA were found in fish that consumed Diet C compared to Diet D. These findings support the hypothesis that the inclusion of seaweed in fish farm diets alters lipid partitioning and profiles of Atlantic salmon. Practical Applications: This study reveals a possible way to substantially increase EPA and DHA concentrations in farmed salmon. Both EPA and DHA are LC n ‐3 PUFAs and are essential components of the human diet. Unfortunately, consumption of such PUFAs is generally below RDI levels, which is in turn linked to several non‐communicable diseases. Moreover, EPA + DHA concentrations in farmed salmon are now declining due to the replacement of scarce fish oils (rich in LC n ‐3 PUFA) by more sustainable plant‐based oils (low in EPA + DHA) in ...